Foreign direct investment and economic development - Singh, Ravishankar Kumar (ed.); Kulkarni, V.S. (ed.) (Delhi, 2006)
With the advent of continuous economic reforms the economy has recorded average growth rate of around 6% in the last decade. One major reform that has taken place in the area of attracting foreign investment into India, via either the foreign direct investment (FDI) route or from foreign institutional investors (FIIs). FDI is very stable by nature as it usually enters for long-term projects. It also helps to generate employment and bring in the latest technological inventions/ advancements. FIIs, on the other hand, usually help in developing capital markets. Entrepreneurs can tap the capital market by wooing FIIs and can thereby set up new projects or use the funds for expansion, etc. However, FII investment may not be very stable; there can be sudden outflows if capital markets perform adversely, or are expected to perform negatively. Even in the South-East Asian economic crisis-in countries like Thailand, and Indonesia-it had been the FIIs who had disturbed growth trends by creating sudden outflows of forex reserves, thereby resulting in the devaluation of the local currency. The Govt. of India has set for itself the target of achieving $10 billion in FDI inflows per year. As per present guidelines, FIIs can invest in shares of Indian companies subject to maximum ceiling to 24% of the issued share capital of a company. Both FDI and FIIs bring in valuable capital and must be encouraged by suitable policy amendments. The Govt. should consider both as the same while finalising capital expenditure for investment in companies/ projects. Yet, due to the factors enumerated above, FDI is more suitable for a country like as compared to FIIs as the latter is short India term and volatile. Learned contributors in this book seek to explore various aspects of Foreign Direct Investment in country and how it is related to the economic development, employment generation, infrastructure development and the impact of FDI on a country as a whole.
Keywords: Economic development